MicroRNA‐92b‐3p is a prognostic oncomiR that targets TSC1 in clear cell renal cell carcinoma. Issue 4 (19th February 2020) - Wang, Cong; Uemura, Motohide; Tomiyama, Eisuke; Matsushita, Makoto; Koh, Yoko; Nakano, Kosuke; Hayashi, Yujiro; Ishizuya, Yu; Jingushi, Kentaro; Kato, Taigo; Hatano, Koji; Kawashima, Atsunari; et al.
Abstract: Although several studies have reported that microRNA (miR)‐92b‐3p is involved in various cellular processes related to carcinogenesis, its physiological role in clear cell renal cell carcinoma (ccRCC) remains unclear. To clarify the role of miR‐92b‐3p in ccRCC, we compared miR‐92b‐3p expression levels in ccRCC tissues and adjacent normal renal tissues. Significant upregulation of miR‐92b‐3p was observed in ccRCC tissues. Overexpression of miR‐92b‐3p using a miRNA mimic promoted proliferation, migration, and invasion activities of ACHN cells. Functional inhibition of miR‐92b‐3p by a hairpin miRNA inhibitor suppressed Caki‐2 cell growth and invasion activities in vitro. Mechanistically, it was found that miR‐92b‐3p directly targeted the TSC1 gene, a known upstream regulator of mTOR. Overexpression of miR‐92b‐3p decreased the protein expression of TSC1 and enhanced the downstream phosphorylation of p70S6 kinase, suggesting that the mTOR signaling pathway was activated by miR‐92b‐3p in RCC cells. Importantly, a multivariate Cox proportion hazard model, based on TNM staging and high levels of miR‐92b‐3p, revealed that miR‐92b‐3p expression (high vs. low hazard ratio, 2.86; 95% confidence interval, 1.20‐6.83; P  = .018) was a significant prognostic factor for overall survival of ccRCC patients with surgical management. Taken together, miR‐92b‐3p was found to act as an oncomiR, promoting cell proliferation by downregulating TSC1 in ccRCC. Abstract : MicroRNA‐92b‐3p was found to act as an oncomiR, promoting cell proliferation by downregulating TSC1 in clear cell renal cell carcinoma, and predicts poor patient overall survival.